Model Penahan Ketinggian Quadrotor Berbasis PID dengan Jaringan Syaraf Tiruan Propagasi Mundur - Faisal Fajri Rahani; Dinan Yulianto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
A quadrotor is a type of Unmanned Aerial Vehicle (UAV) or an unmanned flying vehicle flying remotely or using automatic control. In carrying out its mission, a quadrotor requires a good control system. One of the control systems in the quadrotor system is the altitude control system. Altitude control will control the quadrotor according to the desired altitude, whether there are interference and the quadrotor load. The widely used control method is the PID control. Unfortunately, the PID control produces a poor response because the PID constant is fixed, whereas the interference when the quadrotor flies will fluctuate. Therefore, this study offers control that can make a self-adjustment when exposed to specific interference. The method offered in this study is a PID control with Artificial Neural Networks (ANN). The ANN system will tune the PID components in real-time according to the occurring interference. The use of the PID with ANN results in a faster rise time response of 0.0594 seconds, a decrease in overshoot of 7.58%, a decrease in the steady-state error of ± 0.0672, and a decrease in settling time of 1.031 seconds compared to conventional PID. It shows that the PID with ANN results in better control than the PID alone.